Transcriptional requirements of the distal heavy-strand promoter of mtDNA - Zollo, Ornella (National Academy of Sciences, 2012)
The heavy strand of mtDNA contains two promoters with nonoverlapping functions. The role of the minor heavy-strand promoter (HSP2) is controversial, because the promoter has been difficult to activate in an in vitro system. We have isolated HSP2 by excluding its interaction with the more powerful HSP1 promoter, and we find that it is transcribed efficiently by recombinant mtRNA polymerase and mitochondrial transcription factor B2. The mitochondrial transcription factor A is not required for initiation, but it has the ability to alternatively activate and repress the HSP2 transcriptional unit depending on the ratio between mitochondrial transcription factor A and other transcription factors. The positioning of transcriptional initiation agrees with our current understanding of HSP2 activity in vivo. Serial deletion of HSP2 shows that only proximal sequences are required. Several mutations, including the disruption of a polycytosine track upstream of the HSP2 initiation site, influence transcriptional activity. Transcription from HSP2 is also observed when HeLa cell mitochondrial extract is used as the source of mitochondrial polymerase, and this transcription is maintained when HSP2 is provided in proper spacing and context to the HSP1 promoter. Studies of the linked heavy-strand promoters show that they are differentially regulated by ATP dosage. We conclude that HSP2 is transcribed and has features that allow it to regulate mitochondrial mRNA synthesis.